Pemertahanan Adat Bali dan Moderasi Beragama pada Masyarakat Kampung Bali, Kabupaten Langkat - Muhammad Hendry Devano; Linawati Linawati; Hafiz Alif Oemar; Rachmad Abduh (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to determine the maintenance of the Balinese language by the third generation of Langkat Balinese transmigrants, to determine the religious moderation of Muslims and Hindus in the Balinese Village community in Langkat Regency, to determine the maintenance of Balinese customs by the third generation of the Balinese tribe in Langkat Regency. This research problem is focused in the third generation of Balinese tribal people who live in North Sumatra and Islamic communities in Kampung Bali. In order to approach this problem, customary theory and religious moderation were used, data was collected through literature surveys, observations and interviews and analyzed qualitatively using an ethnographic approach. This research concludes that the Balinese people who have lived in North Sumatra since 1963 have reached several generations, currently they have reached the third and fourth generations, the use of the Balinese language in the third generation has experienced a significant decline, but in terms of maintaining customs, many traditions are still maintained despite simplification. . The Balinese Hindu community also carries out religious moderation which creates harmony between religious communities. The attitudes of the people of Kampung Bali Langkat are in line with the moral teachings of the Hindu religion, namely Tat Twam Asi. Religious moderation is also carried out by Muslims according to the principles of the Islamic religion.